Analisis Ekonomi Islam tentang Perilaku Konsumtif Mahasiswa Fakultas Ekonomi dan Bisnis Islam UIN Alauddin Makassar - Rahayu, Andi Sri; Kara, Muslimin; Katman, Muh. Nasri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2023)
This study is entitled "Islamic Economic Analysis of Consumptive Behavior of Students of the Faculty of Islamic Economics and Business Uin Alauddin Makassar." The data source used is primary data, namely information that comes from direct observation at the research location after conducting observations and interviews. Meanwhile, secondary sources are data obtained from documentation or literature studies to complement primary data. Data collection was carried out by field research through observation, interviews, and documentation. The results of this study indicate that generally, students are more likely to behave consumptively than those who do not based on the three forms of consumptive behavior, namely in terms of food, shopping for "fashion" appearances, and ways to fill free time such as shopping malls, and others. The review of Islamic Economics has not been properly implemented by students, as from the data obtained that some student expenses are greater than reporting, students often buy food and then don't finish it or buy things that are not really needed, this kind of thing is classified as a waste which is prohibited in Islam. Therefore it takes awareness from everyone, especially students to apply consumption behavior that has been taught in Islam. Keywords : consumptive economy.